Analytical Study to Produce The Green Hydrogen Via Wind Energy in Malaysia - BIN ZAINUREN, MUHAMAD AMIRUN AQIL; SADEQ, TAHA (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The study explores the possibility of generating green hydrogen using wind power in Malaysia. It revolves around incorporating wind-driven electrolysis as one of the hydrogen production avenues that comply with the decarbonization targets in Malaysia. The issues facing integration of wind and hydrogen are severe wind speed, a deficiency of special turbine technologies and a know-how gap, which are mentioned. The process will include the modelling of wind turbines and hydrogen plant, gathering data on wind profiles of cities chosen in Malaysia, and simulations with MATLAB Simulink to evaluate the rates of production. Findings indicate that there is a potential of introducing hybrid renewable system to increase the reliability and efficiency of hydrogen generation, despite the moderate wind climate in Malaysia. The results present knowledge to develop a local green hydrogen structure.